The Anti-Inflammatory and Anti-Pruritus Mechanisms of Huanglian Jiedu Decoction in the Treatment of Atopic Dermatitis - Xu, Yubin; Chen, Saizhen; Zhang, Lingling; Chen, Guirong; Chen, Jinguang (Frontiers in Pharmacology, 2021)
Atopic dermatitis (AD) is a common chronic skin disease driven by a T cell-mediated immune response, with inflammation and pruritus being its main clinical manifestations. Huanglian Jiedu Decoction (HLJDT), which is an ancient Chinese medicine herbal formula derived from Wai-Tai-Mi-Yao, is a potentially effective treatment for AD. We aimed to clarify the anti-inflammatory and anti-pruritus mechanisms of HLJDT in AD treatment. We performed immunohistochemistry, western blotting, reverse transcriptase-polymerase chain reaction, Luminex-based direct multiplex immunoassay, enzyme-linked immunosorbent assays, and flow cytometry to address the abovementioned aims. HLJDT significantly reduced clinical symptoms and ear swelling in AD-like mice by inhibiting the production of cytokines (histamine, interleukin [IL]-3, IL-4, IL-5, IL-13, IL-17A, IL-31, and IL-33), substance P (SP), transient receptor potential cation channel subfamily V member 1 (TRPV-1), and gastrin-releasing peptide (GRP). Additionally, HLJDT significantly suppressed the protein expression levels and positive cell percentage of CD28, CD80, CD86, CD207, CD326, MHCII, and OX40 in lymphoid nodes. Moreover, HLJDT significantly suppressed mRNA and protein expression of tyrosine-protein kinase (JAK1), histamine H4 receptor, and IL-4Rα, as well as the protein expression of GRP, SP, and TRPV-1 in the root ganglion. Our findings indicate that HLJDT can treat AD by regulating the antigen presentation function of dendritic cells, weakening T lymphocyte activation, and subsequently exerting anti-inflammatory and anti-pruritus effects.